2019
DOI: 10.1182/bloodadvances.2018027748
|View full text |Cite
|
Sign up to set email alerts
|

PTCy-based haploidentical vs matched related or unrelated donor reduced-intensity conditioning transplant for DLBCL

Abstract: This study retrospectively compared long-term outcomes of nonmyeloablative/reduced intensity conditioning (NMC/RIC) allogeneic hematopoietic cell transplantation (allo-HCT) from a haploidentical family donor (haplo-HCT) using posttransplant cyclophosphamide (PTCy) with those of matched sibling donor (MSD) and matched unrelated donor (MUD) with or without T-cell depletion (TCD+/TCD−) in patients with relapsed diffuse large B-cell lymphoma (DLBCL). Adult patients with DLBCL who had undergone their first NMC/RIC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 44 publications
3
64
0
Order By: Relevance
“…The final analysis included 17 studies ( Figure 1). One study was a prospective phase 2 trial [19], while the remaining 16 studies were retrospective multi-center, registry, or single-center studies [14,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. This included 13957 patients who underwent Haplo-SCT (2012 patients) or MUD-SCT (11945 patients).…”
Section: General Description Of Included Studiesmentioning
confidence: 99%
“…The final analysis included 17 studies ( Figure 1). One study was a prospective phase 2 trial [19], while the remaining 16 studies were retrospective multi-center, registry, or single-center studies [14,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. This included 13957 patients who underwent Haplo-SCT (2012 patients) or MUD-SCT (11945 patients).…”
Section: General Description Of Included Studiesmentioning
confidence: 99%
“…1 Fortunately, development of Haplo-HCT using post-transplant cyclophosphamide (PTCy) significantly improved the rates of graft-versushost disease (GvHD), non-relapse mortality and engraftment. [2][3][4][5][6][7] Compared with Allo-HCT with matched related or unrelated donor, retrospectives studies reported similar overall survival (OS) and disease-free survival (DFS) with Haplo-HCT and even sometimes a decreased incidence of acute and/or chronic GvHD. [2][3][4][5][6][7] PTCy acts through induction of functional impairment of alloreactive T cells without toxic effects on haematopoietic stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…RESULTS: Nearly all (98.4%) patients were transfused in the first 30 days, and 59.2% were transfused between days 31 and 100. Among the transfused patients, medians of 5 units (interquartile range [IQR] = 3-8) of RBCs and 11 units (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) platelets were given in the first 30 days, and medians of 3 units (IQR = 1-7) of RBCs and 6 units (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) of platelets were transfused between days 31 and 100. Median times for achieving RBC and platelet transfusion independence were 34 (95% CI: [28][29][30][31][32][33][34][35][36][37][38][39][40]) and 25 (95% CI: 23-27) days, respectively.…”
mentioning
confidence: 99%
“…1 Multiple single center and registry-based studies have compared transplant outcomes (including engraftment, relapse, survival, incidence, and severity of graft-versus-host disease [GVHD]), of haplo-HSCT recipients to MRD and MUD recipients with a variety of hematological diseases, and the results thus far have been encouraging and favorable. [7][8][9][10][11][12][13][14][15][16] Further prospective and retrospectives studies are still ongoing.…”
mentioning
confidence: 99%